Correlation Between Maternal Anaemia and Birth Weight of Neonates: Experience of A Tertiary Care Hospital - Kamal, MA (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Maternal anaemia is a common health concern and has frequently been associated with low birth weight (LBW) in newborns. Anaemia during pregnancy can lead to adverse birth outcomes, including prematurity, low birth weight (LBW), and increased risk of neonatal mortality. Objective: To determine the correlation between maternal anaemia and neonatal birth weight. Methodology: This observational study was conducted in the department of Neonatology, Bangladesh Shishu Hospital & Institute (BSH&I), over a period of six months from January 2023 to June 2023. The sample size consisted of 100 participants, 47 women with maternal anaemia and 53 without anaemia . Newborns were included in the study if they were born to mothers aged between 18 and 40 years, had a gestational age of 37 weeks or more had complete medical records from the third trimester through delivery. Results: Low birth weight was observed in 30(63.8%) infants born to anemic mothers and 21(39.6%) infants born to non-anemic mothers. This difference was statistically significant (p<0.01). Positive correlation (r=0.478; p=0.001) between maternal haemoglobin and birth weight was found. Conclusion: Infants born to anemic mothers had a significantly higher incidence of low birth weight compared to those born to non-anemic mothers, with a positive correlation observed between maternal hemoglobin levels and neonatal birth weight. DS (Child) H J 2024; 40(1): 41-45